(untitled) (RUNA, archivo para las ciencias del hombre, 2014)
Evaluadores Extranjeros Ruy Llera Blanes – University of Bergen, Noruega Josep Martí – Institució Milà i Fontanals /CSIC, España Enrique Cámar de Landa – Universidad de Valladolid, España Osvaldo Meira Trigueiro – Universidade Federal da Paraíba,Brasil Paola Ponce - Durham University, Inglaterra Evaluadores Nacionales Nicolas Viotti – UCA / CONICET Jorge Suby – Dep. Arq. UNCPBA Ana Ramos – IIDyPCA, UNRN / CONICET Claudia Salomon Tarquini – IES, UNLPam / CONICET Mirta Bialogorski – Museo de Arte Popular José Hernández / GCBA Graciela Bailliet – IMBICE/ CONICET Noemí Acreche – UNSa